Establishment of a hospital-acquired infection surveillance system in a teaching hospital in Rwanda - Lukas, Stephanie; Hogan, Unarose; Muhirwa, Viatory; Davis, Caroline; Nyiligira, John; Ogbuagu, Onyema; Wong, Rex (International Journal of Infection Control, 2016)
Hospital-based infection surveillance and control programs can reduce hospital acquired infection (HAI) prevalence. In resource-limited countries, HAI surveillance is challenging to implement due to inadequate or lacking laboratory infrastructure and trained personnel. A HAI surveillance system was implemented in a teaching hospital in Rwanda. A multi-disciplinary team developed a point-prevalence HAI surveillance tool based on World Health Organization (WHO’s) criteria and conducted surveillance on all inpatient units from September 2013 to March 2014. The baseline HAI rate was 15.1%. Highest HAI rates were found in intensive care unit (ICU) (50.0%), Neonatal ICU (23.1%) and Orthopedics/burn unit (37.3%). Factors significantly associated with increased risk of developing HAIs included surgery within the past month (odds ratio [OR] 2.75, 95%CI: 1.40, 5.40), use of a urinary catheter (OR 2.10, 95%CI: 1.05, 4.25), use of mechanical ventilator (OR 3.14, 95%CI: 1.01, 9.74), and use of chest drain, naso-gastric tube, external fixator (OR=3.93). Longer hospital length of stay was also significantly associated with a risk of HAI (OR 1.02). It is feasible in a low-resource setting to establish HAI surveillance and obtain an accurate HAI rate. The surveillance information can inform prioritization of infection prevention efforts.